Understanding the health-related quality of life and treatment-related side-effects in patients who have been in remission from testicular cancer for 12–24 months - Cazzaniga, Walter; Kinsella, Janette; Pearce, Adam Kieran; Moghul, Masood; Fox, Louis; Van Hemelrijck, Mieke; Reid, Alison; Huddart, Robert; Nicol, David (Frontiers in Urology, 2023)
Introduction Despite the excellent long-term prognosis after treatment for testicular cancer (TCa), therapy-related side effects can be persistent and severe. The aim of this study was to determine the nature and prevalence of post-treatment symptoms and their impact on health-related quality of life (HRQoL) in TCa patients 12 to 24 months after treatment. Materials and methods Cross-sectional, single-center study. All patients who were aged 18 and over, had completed TCa treatment 12–24 months previously and had no evidence of disease recurrence were considered eligible. Participants were stratified into four groups: 1) orchidectomy only; 2) orchidectomy and single dose adjuvant carboplatin; 3) multi-agent induction chemotherapy (CBOP-BEP, BEPx3 or x4, or Epx4 regimens); and 4) post-chemo retroperitoneal lymph node dissection (PC-RPLND). Eligible patients were asked to complete the EQ-5D-5L questionnaire and the EORTC QLQ-TC26 questionnaire. We performed a thematic analysis of free-text commentary to evaluate the sensitivity of PROMs used across the treatment groups. Descriptive results were reported. For categorical variables, numbers and percentages were used, and for continuous variables median and IQR values were used. Results The EQ-5D-5L questionnaire showed that patients treated with orchidectomy only and orchidectomy and adjuvant carboplatin experienced only minor physical medium- to long-term side-effects. In contrast, more intensive treatment regimens, such as multi-agent chemotherapy or PC-RPLND, were associated with a higher burden of medium- to long-term side-effects. Similar results were obtained with the EORTC QLQ-TC26 questionnaire. Conclusions This study reports the medium- to long-term HRQoL and side effects of TCa treatments, using both EQ-5D-5L and EORTC QLQ-TC26 questionnaires, and identifies possibly “unasked” questions from a patient perspective in relation to supportive care needs following TCa treatment. This information will help clinicians to better understand the consequences of treatment and in turn provide better patient counseling before treatment.